Avaliação das oportunidades de estimulação motora nos centros municipais de educação infantil (CMEI) em região de fronteira - Hanzen, Debora Cristina Santana (2022)
INTRODUCTION: During children’s development, they undergo sensory-motor experiences that contribute to acquire motor and cognitive skills, provided by the context in which they are inserted. Ergo, it is understood that institutions aimed at early childhood education should offer a planned and stimulating learning environment. OBJECTIVE: To evaluate the motor stimulation opportunities offered to children at the Municipal Education of Daycare nursery Centers (CMEI in Portuguese) of a border city. METHODS: It is a descriptive study with a quantitative-qualitative approach. The studied sample consisted of 22 CMEIs in, Foz do Iguaçu/PR city, which had their nursery classes evaluated using AHEMD-IS Context Daycare (from 03 to 18 month-age children) as a research tool. The results classified the institution as poor, adequate or good for motor stimulation opportunities. RESULTS: From the twenty two Centers, thirteen of them were classified as "adequate" (59%), six were classified as "poor" (27%) and three institutions were classified as "good" (14%). When the results were compared in relation to the location where the CMEIs are inserted in the municipality, it was possible to observe that the CMEIs with the highest and lowest classification are quite scattered throughout all areas of the studied city. CONCLUSION: According to the results, the vast majority of the studied centers were classified as “adequate”, which leads us to realize that there is a need for adjustments and improvements to provide quality motor and sensory stimuli to children who are inserted in childcare and teaching institutions. From this point on, new projects may arise in order to adapt and provide greater quality to children inserted at Municipal Education of Daycare nursery Centers.